1991
DOI: 10.1007/bf01993295
|View full text |Cite
|
Sign up to set email alerts
|

Effect of capsaicin on carrageenan-induced inflammation in rat pleurisy and exudate substance P level

Abstract: Injection of 2.5 mg of lambda-carrageenan into the rat pleural cavity resulted in a time-dependent increase in pleural exudate substance P (SP) levels up to 24 hr. Synergistic increases in the exudate formation were observed when a sub-optimal quantity of carrageenan was injected with SP. Pre-treatment of rats with capsaicin at 50 and 100 mg/kg s.c. daily for one week prior to the induction of pleurisy blocked the increase in exudate volume and SP levels when compared to that normally detected after carrageena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…The complement factors play a minor role (28,29,32), but the involvement of neutrophils (32) and the kinin system (28, 33) has been demonstrated. In addition, there is evidence for a tachykinin neurogenic component (34)(35)(36). Our results demonstrated a small but significant decrease in edema formation in knockout compared with wild-type mice, but a substantial and highly significant decrease in neutrophil accumulation.…”
Section: Discussionsupporting
confidence: 49%
“…The complement factors play a minor role (28,29,32), but the involvement of neutrophils (32) and the kinin system (28, 33) has been demonstrated. In addition, there is evidence for a tachykinin neurogenic component (34)(35)(36). Our results demonstrated a small but significant decrease in edema formation in knockout compared with wild-type mice, but a substantial and highly significant decrease in neutrophil accumulation.…”
Section: Discussionsupporting
confidence: 49%
“…Calcium ionophore A 23187 was purchased from Calbiochem, La Jolla, CA. Pleurisy was induced as described earlier [7]. Calcium ionophore A 23187 (100 nmol) solubilized in DMSO and phosphatebuffered saline (PBS) (1 : 1) was injected intrapleurally in a volume of 0.2 ml.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, a lot of studies have shown that, in other systems, allergic and inflammatory responses have a neurogenic component which is capsaicin-sensitive [27][28][29][30][31],…”
Section: Discussionmentioning
confidence: 99%